TypePad for dummies - Nelson, Melanie, 1971- (--For dummies., 2010)
"If you've been thinking about breaking into the blogo-sphere but didn't know where to start, you've come to the right place. First, you'll get some pointers on what blogging's all about and how to develop your online identity. Then you'll find out how TypePad works, how to use TypeLists and widgets, and what it takes to make your blog a huge success!"--Resource description page